A beam-column model for evaluating the effects of residual stresses and geometrical imperfections. (15th October 2019) - Melo, P.; Vieira, R.F.; Virtuoso, F.B.
Highlights: A numerical model for the geometric and non-linear analysis of beam-columns. Modelling of residual stresses and nonlinear material through distributed plasticity. Eurocode 3's applicability to determine the resistance of columns and beam-columns. Modelling of columns residual stresses. Influence of geometrical imperfection's direction relatively to the longitudinal weld. Abstract: A numerical model within the framework of the finite element method is developed in order to perform second order analyses of steel columns and beam-columns by considering geometrical and material nonlinearities, and taking into account residual stresses and initial geometric imperfections. The model considers a displacement based beam element and adopts a distributed-plasticity formulation for the implementation of the steel nonlinear behaviour together with a Newton-Raphson algorithm for the solution of the resulting nonlinear governing equations. The results obtained from the developed model are compared with the results in the literature that were adopted for the calibration of the formulae in Eurocode regarding the buckling resistance of columns and beam-columns. Thereafter, the model is adopted to evaluate the applicability/accuracy of these formulae regarding the corresponding safety check. A detailed evaluation of the buckling resistance of columns with tubular cross-sections is presented, namely in what concerns the effect of the relative position of the longitudinal fillet weld to the direction of the considered geometric imperfection.